The pathway to Viral Hepatitis Elimination – Where are we in Africa? - Wendy Spearman (International Journal of Infectious Diseases)
In 2016, WHO set a goal to eliminate Hepatitis B and C by 2030, reducing the incidence by 90% and mortality by 65%. Yet in 2022, there was estimated 254 million people living with hepatitis B and 50 million living with hepatitis C; with 1.2 million new hepatitis B infections and nearly 1.0 million hepatitis C infections. However, only 13% of people living with chronic hepatitis B had been diagnosed and 2.6% received antiviral therapy. Only 36% of people living with hepatitis C had been diagnosed between 2015 and 2022, and 20% received curative treatment.In the WHO Africa region, 64.7 M are estimated to be HBV-infected with 771 000 new infections but only 4.2% had been diagnosed and 0.2% had received treatment. The WHO Africa Region accounts for 66% of new hepatitis B infections, and yet only 18% of newborns receive the preventative hepatitis B birth-dose vaccination.7.8 million people are estimated to be living with Hepatitis C in the WHO Africa region but only 13% have been diagnosed and 3% have received curative Direct acting antiviral therapy.Achieving the WHO 2030 targets will globally save 2.85 million lives and avert 9.5 million new infections and 2.1 million cases of cancer. To address the burden of viral hepatitis in WHO Africa, we need to implement the Hepatitis B birth dose vaccine, decentralise management with affordable point-of-care diagnostics, simplified treatment algorithms with universal access to affordable antiviral therapies.